Adskillelse og vekselvirkning. Om Grundtvigs syn på folkelighed og kristendom - Jørgensen, Theodor Holzdeppe (Grundtvig-studier, 1986)
Separateness and Interaction. Grundtvig’s Ideas on the Character of the People and Christianity By Professor Theodor Jørgensen, DD, Copenhagen Separateness and interaction are central concepts in Grundtvig’s definition of the relationship between the character of the people and Christianity. He makes a sharp distinction between the two to ensure that the relationship between them remains a free one. It is important for Christianity, which does not want to rule but to serve the people. But this sharp distinction does not mean that Grundtvig understands the character of the people as a purely secular quantity. He sees it as spiritual, where spiritual contains the human spirit, the spirit of truth and the Holy Spirit. Regarded in this light the character of the people constitutes the prerequisite for Christianity, because it contains, albeit in broken form, the God-created humanity that is reborn in Christianity. At the deepest level the life-source in the character of the people and in Christianity is the same, i.e. God; or rather, God the Holy Spirit. And the interaction between them is God’s meeting with Himself in His creation. It is important to insist that the interaction works both ways, a fact often forgotten through a one-sided interpretation of Grundtvig’s basic principle: First a Man, then a Christian. The character of every people adds to Christianity a new faceting of its content through the gospel being preached in the native language and becoming concrete in its natural imagery. In return, Christianity adds to the character of every people the living hope in Christ, making it through Him a reborn character. Grundtvig’s view of the relationship between the two corresponds to the relationship nowadays between life-philosophy and faith. Faith receives a concretion from lifephilosophy. On the other hand there are fundamental human values, originally existing free of Christianity, which today are best defended by faith. Here faith acquires a political perspective.